The confrontation between the Archbishop of Cape Town, Joost de Blank, and the South African government on racial policies, 1957-1963 - Paine, Victor C (Department of Religious Studies, 2016)
This study arises partly out of a pre-occupation with a period covering six impressionable years of my life - the final year at school, university days and the commencement of a teaching career; and partly from a reading of Alan Paton's Apartheid and the Archbishop which in covering the political aspects of Geoffrey Clayton's archbishopric inspired me to attempt the same for the term of Joost de Blank. The racial legislation passed since 1948 is discussed at the outset as it is the backdrop against which the whole Confrontation must be viewed. The reader might stagger under the sheer weight of detail but this is my intention since it facilitates an identification with de Blank who was overwhelmed by a plethora of legislative acts. The Anglican background to the period under discussion is of moment in that it reveals how de Blank became embroiled in a Church-State relationship which had gradually, yet perceptibly, deteriorated. Much of the material here is based on my own study of Synodal Resolutions and the Charges of Geoffrey Clayton. The biographical chapters provide the reader with the necessary factual background and, at the same time, make an independent judgement possible. de Blank's theological insights detected in the works written before his Enthronement furnish the categories into which the Confrontation naturally falls. This must be stressed because it is my conviction that de Blank's attack on apartheid represents not a departure from, but an extension of his earlier views, In conclusion, the Assessment examines the achievement of the Archbishop largely, but not exclusively, in the light of his own theological criteria.